Implementasi Knowledge Management System Pada Bank Tabungan Negara di Provinsi Sumatera Selatan - Fery Antony (UNIVERSITAS INDO GLOBAL MANDIRI)
ABSTRACTThis study discusses the Implementation of Knowledge Management System (KMS) at the National Savings Bank (BTN) in South Sumatra, as a government bank. Given the role of banks in the economy and the extraordinary level of competition. This research is expected to be a reference in implementing KMS in banking. Banks need KMS to run business processes in the application of expertise in organizations, because KMS is able to improve the bank's core competencies. KMS acts as a liaison in the knowledge provider to broaden and deepen knowledge, contribute to overcoming competition between banks in raising funds to create forms of innovative product services provided to the public. This research is to identify the implementation of KMS in the organization, so it can be seen the success factors of KMS in banking institutions. Data collected by questionnaire, then made a research model. The survey results revealed that the KMS model suitable for use as a reference model for KMS implementation in BTN South Sumatra was influenced by factors, namely KM; organizational factors measurement objectives / specific strategies and leadership support, information technology and service innovation to consumers.Keywords : Implementation KMS, KMS on Banking, KMS Success FactorsABSTRAKPenelitian ini membahas Implementasi Knowledge Management System (KMS) di Bank Tabungan Negara (BTN) di Sumatera Selatan, sebagai Bank pemerintah. Mengingat peran bank dalam perekonomian dan tingkat persaingan yang luar biasa. Penelitian ini diharapkan dapat menjadi referensi dalam mengimplementasikan KMS di perbankan. Bank membutuhkan KMS untuk menjalankan proses bisnis dalam penerapan keahlian dalam organisasi, karena KMS mampu meningkatkan kompetensi inti bank. KMS bertindak sebagai penghubung dalam penyedia pengetahuan untuk memperluas dan memperdalam pengetahuan, berkontribusi untuk mengatasi persaingan antara bank dalam mengumpulkan dana untuk menciptakan bentuk-bentuk layanan produk inovatif yang disediakan untuk publik. Penelitian ini untuk mengidentifikasi implementasi KMS dalam organisasi, sehingga dapat dilihat faktor keberhasilan KMS di lembaga perbankan. Data yang dikumpulkan dengan kuesioner, kemudian dibuat model penelitian. Hasil survei mengungkapkan model KMS yang cocok untuk digunakan sebagai model referensi implementasi KMS di BTN Sumatera Selatan dipengaruhi oleh faktor-faktor, yaitu KM; faktor organisasi tujuan pengukuran / strategi tertentu dan dukungan kepemimpinan, teknologi informasi dan inovasi layanan kepada konsumen.Kata kunci : Implementasi KMS, KMS di Perbankan, Faktor Keberhasilan KMS